Survival of the city : living and thriving in an age of isolation - Glaeser, Edward L; Cutler, David M (London : Basic Books, 2021)
"In Survival of the City, an urbanist and a public health expert join forces to explain where cities are right now and provide a prescription for a healthy future for them"--
Keywords: City and town life -- United States; Urban health -- United States; Epidemics; COVID-19 Pandemic, 2020- -- United States; COVID-19 Pandemic, 2020- -- United States; Urban economics; Urban policy -- United States